Management of The CFA Franc: What are the Fundamentals of the Real Exchange Rate in West African Economic and Monetary Union (WAEMU)? - Wonyra, Kwami Ossadzifo; Tenakoua, Honore (The Economics and Finance Letters, 2020)
Identifying the fundamentals of the real exchange rate of the CFA franc in West African Economic and Monetary Union (WAEMU) is the main objective of this paper. To achieve this, we used panel data over a period from 1984 to 2014. To achieve this objective, we use the Pooled Mean Group, inspired by the work of Pesaran, Shin, and Smith (1999) with data from secondary sources from the World Bank and the International Monetary Fund. The results obtained show that investment, government spending, trade openness and balance significantly influence the real exchange rate of the long-term CFA franc in WAEMU. With regard to the short-term relationship, the results show that only productivity and the trade balance are the fundamentals that significantly influence the real exchange rate of the CFA franc. It is then necessary to find a solution to this extroversion of WAEMU economies, which solution would be the promotion of the import substitution policy. A policy should be put in place to enable our economies to benefit from trade liberalization. This involves promoting exports of high value-added products in order to improve the external position of economies and to address the instability of commodity prices on which developing country exporters of primary goods depend.